Pengaruh Kualitas Layanan Terhadap Kepuasan Anggota (Studi Kasus Pada KSP PARAMA – Para Raya Mayapadha) - Soesy Mayang Sary (BIMA : Journal of Business and Innovation Management, 2019)
This study aims to determine the quality of service to member satisfaction using associative descriptive quantitative methods, this study only looks for differences between the independent variables on the dependent variable only. The results of this study indicate that the quality of services consisting of significant physical evidence, reliability, responsiveness, and empathy and guarantees do not significantly influence member satisfaction at KSP PARAMA (Para Raya Mayapadha).